Efektivitas Metode Eklektik dalam Pembelajaran Mahfuzhot: Studi Kasus - Tomo, Yarkoni Budi; Putra, Sudarmadi (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This study aims to analyze the implementation and effectiveness of the eclectic method in learning Mahfuzhot in Class VIIIB of MTs Islam Ngruki. The main focus is on improving the understanding and learning outcomes of Mahfuzhot, as well as identifying the strengths and weaknesses of the method.Method – An exploratory and descriptive naturalistic qualitative research was conducted, using observation, interviews, and documentation techniques. The Miles and Huberman method was used for data analysis, including data reduction, presentation in the form of graphs/charts, and conclusion. Triangulation of sources and methods was applied to ensure the reliability and validity of data.Findings – The integration of qawaid tarjamah, mubasyar, and sam’iyyah syafahiyyah methods resulted in improved material understanding. Despite constraints in learning time and student readiness, an increase in lesson absorption from 50% to 57% was recorded. This study reveals the effectiveness of the eclectic method in improving Mahfuzhot's learning outcomes. Research Implications – These findings have important implications in Arabic language teaching practices, highlighting the need for flexibility and creativity in teaching approaches. Time constraints, learning facilities, and student engagement mark the limitations of this study. Further research is recommended to optimize Arabic language teaching strategies, overcome challenges in learning Mahfuzhot, and improve the overall quality of education.